Kritik af forestillingen om et godt liv - Rosfort, René (Dansk Teologisk Tidsskrift, 2014)
This article examines the complex relation between naturalism, ethics, and ideas of a good life, in order to argue for the relevance of a Christian ethics in an age of naturalism. The first two sections deal with the question of naturalism. While strict naturalism maintains a view of nature based on the meaninglessness of nature, relaxed naturalism advocates a more pragmatic view of nature that allows for human meaning and practice. I argue that a relaxed form of naturalism is highly problematic due to its pragmatic emphasis. I also argue that a pragmatic naturalism is not able to answer two basic ethical demands, namely the demand of universalism and the demand of freedom. In the third and final section I sketch my view of a Christian ethics that is able to answer these demands. This ethics takes the form of a critique of our ideas of a good life, arguing that living ethically is a constant struggle both against and for the fragile character of human freedom. It is a radical ethics about the difficult work of human freedom for a hope of humanity that has no solid foundation and no clear answers.